2C.01: FIXED RANKING OF LEUKOCYTE TELOMERE LENGTH IN ELDERLY PEOPLE. (June 2015) - Toupance, S.; Watfa, G.; Lakomy, C.; Kearney-Schwartz, A.; Labat, C.; Rossignol, P.; Lacolley, P.; Zannad, F.; Benetos, A.
Abstract : Objective: Short leukocyte telomere length (LTL) is associated with atherosclerosis in adults and diminished survival in the elderly. The prevailing view is that LTL is associated with accelerated aging since it serves as a biomarker of the cumulative burden of inflammation and oxidative stress during adult life. However LTL dynamics are mainly defined by LTL at birth, which is highly variable, and its age-dependent attrition thereafter, which is rapid during the first 20 years of life. We examined whether age-dependent LTL attrition during old age can substantially affect individuals' LTL ranking (e.g., longer or shorter LTL) in relation to their peers and which clinical (presence or absence of atheroma) or lifestyle (BMI and smoking) factors can predict it. Design and method: We measured LTL by Telomeric Restriction Fragment Southern Blot (TRF) in samples donated 8 years apart on average by 76 participants of the ADELAHYDE study. Participants were men and women aged 60 to 85 years with a history of hypertension at the inclusion. Results: We observed a mean LTL attrition of 27 bp per year which is consistent with previous data on telomere attrition in adults. No clinical or lifestyle risk factors seem to exert significant effect or can predict LTL attrition in elderly people. We observed a close relationship (r = 0.88) between baseline and follow-up LTL values. Ranking individuals by deciles revealed that 87.5% showed no rank change (38.9%) or only one decile change (48.6%) over time. We observed relationships between baseline values of LTL and BMI as well as between LTL and carotid atheroma. No such relationship was observed between LTL and smoking status. Conclusions: We conclude that in elderly people, LTL ranking changes very little over time. Accordingly, the links of LTL with atherosclerosis and longevity appear to be established early in life. It is therefore unlikely that lifestyle and its modification during old age exert a major impact on telomere length.